SOUTH AFRICAN MARITIME FOREIGN POLICY: RETHINKING THE ROLE OF THE SOUTH AFRICAN NAVY - Blaine, Mark; Nel, Michelle (Scientia Militaria - South African Journal of Military Studies, 2020)
The military is one of the instruments that states use in the implementation of foreign policy within the security domain. As an arm of service, the South African Navy is the instrument of implementation of foreign policy in the maritime domain, playing a role in maritime safety and security as well as environmental protection. Although the concept of a maritime foreign policy is not defined in the literature, Van Nieuwkerk and Manganyi propose a working definition in this publication and it is against the background of this definition that the article reports on the traditional roles and classification of navies against the practical reality of an evolving maritime security context. The discussion then turns towards the maritime threats specific to the Southern African Development Community (SADC) while considering South Africa’s importance within the region and consequent maritime security responsibility. Considering the SADC Maritime Security Strategy and South Africa’s response to maritime insecurity, the study on which this article reports, questioned whether the South African Navy is in fact equipped to deliver on South Africa’s maritime foreign policy in its current de facto role of maritime diplomacy.